AUDIT QUALITY: A MODEL BASED ON PERSONAL CHARACTERISTIC OF AUDITOR ON PUBLIC ACCOUNTING FIRMS - Ceacilia Srimindarti; Pancawati Hardiningsih; Gregorius Anggana Lisiantara; Rachmawati Meita Oktaviani; Ida Ariyani (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2026)
This research uses attribution theory to examine the influence of independence, competence, and integrity on audit quality of auditors’ work at a public accounting firm in Central Java, Indonesia. This study uses a quantitative descriptive research design. The sampling method used in this study is convenience sampling. Data collected through questionnaires distributed directly to auditors working in Central Java. This study involved a sample of 62 auditors from public accounting firms. The data were analyzed using partial least squares analysis. The research results show that audit quality is positively influenced by independence, competence, and integrity. These results can be used as input for partners that improving audit quality can be achieved by increasing the independence, competence, and integrity of their auditors. This article shows how the application of attribution theory can explain how auditors’ personal characteristics can influence audit quality